Phytobiotic Utilization as Feed Additive in Feed for Pancreatic Enzyme Activity of Broiler Chicken - Purwanti, Sri; Zuprizal, Zuprizal; Yuwanta, Tri; Soepadmo, Soepadmo (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2015)
This research was conducted to evaluate the effect of turmeric water extract, garlic and combination turmeric and garlic as a feed additive in the broiler diet on pancreatic enzyme activity of broiler chicken. Effectivity of treatments was assessed by addition of phytobiotic (control, 015% zinc bacitracin, 2.5% TE, 2.0% GE, 2.5% TGE) which were arranged Completely Randomized Design with 4 replications. The variables measured were pancreatic enzyme activity(amylase enzyme activity, protease enzyme activityÂ and lipase enzyme activity).The results showed that enzyme protein activity content of 2.5% TE supplementation is also high at 82.02 U/ml, then supplemented 2.5% TGE, 2.0% GE, negative control and positive control respectively 75.98 ; 72.02; 68.74; and 66.57 U/ml. The lipase enzyme activity whereas the negative control and a positive control differ significantly higher (P<0.05) to treatment with the addition of 2.5% TE, 2.0% GE and 2.5% TGE phytobiotic. The research concluded that the incorporation of 2.5% TE, 2% GE and combined 2.5% TGE as feed additive enhanced pancreatic enzyme activity.